2011
DOI: 10.1088/0004-6256/141/4/132
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Narrowband Tomography of the Local Starburst NGC 1569 With the Large Binocular Telescope/Lucifer

Abstract: We used the near-IR imager/spectrograph LUCIFER mounted on the Large Binocular Telescope (LBT) to image, with sub-arcsec seeing, the local dwarf starburst NGC 1569 in the JHK bands and HeI 1.08µm, [FeII] 1.64µm and Brγ narrow-band filters. We obtained high-quality spatial maps of HeI 1.08µm,[FeII] 1.64µm and Brγ emission across the galaxy, and used them together with HST /ACS images of NGC 1569 in the Hα filter to derive the two-dimensional spatial map of the dust extinction and surface star formation rate den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…This picture is also observed in NGC 1569 (Pasquali et al 2011). In SBS 0335-052 the [FeII] is presumably shocked and at the same location of the HII regions, however our spatial resolution is significantly lower for this galaxy.…”
Section: Discussionsupporting
confidence: 68%
“…This picture is also observed in NGC 1569 (Pasquali et al 2011). In SBS 0335-052 the [FeII] is presumably shocked and at the same location of the HII regions, however our spatial resolution is significantly lower for this galaxy.…”
Section: Discussionsupporting
confidence: 68%
“…3. This pixel probes the part of the cavity seen in both warm ionised and atomic hydrogen observations, but several other cavities in the ISM of smaller scale have been uncovered in the central part of the galaxy (e.g., Pasquali et al 2011). These smaller scale cavities are smoothed out due to the relatively large angular resolution.…”
Section: Ism Cmentioning
confidence: 88%
“…1 2000; Pasquali et al 2011) that has been initially observed in H i (Israel & van Driel 1990 (Tokura et al 2006;Taylor et al 1999;Waller 1991). SC 10, which is not considered an SSC, has a stellar mass of ∼10 3 M⊙ and consists of two components, both with young ages: one of 5-7 Myr, and another with less than 5 Myr (Westmoquette & et al 2007a).…”
Section: Multiwavelength Emission Morphologymentioning
confidence: 98%
See 2 more Smart Citations